2005
DOI: 10.1111/j.1944-9720.2005.tb02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and the True Beginner-False Beginner Dynamic in Beginning French and Spanish Classes

Abstract: This study considered true beginners and false beginners in first‐semester university French and Spanish classes to: (a) determine whether true beginners and false beginners differ in anxiety, grades, and plans to continue language study; and (b) identify classroom factors that foster anxiety or comfort. Students completed a questionnaire that included the Foreign Language Classroom Anxiety Scale (Horwitz, Horwitz, & Cope, 1986), MacIntyre and Gardner Anxiety Subscales (1989, 1994), demographic information, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 38 publications
5
44
0
4
Order By: Relevance
“…Since then, research has been flourishing in this area using the scale as the principal data-collection instrument, agreeing on the existence of anxiety in SL/FL classrooms (Ewald, 2007;Kessler, 2010;Tallon, 2009;Yan & Horwitz, 2008). Though some studies report that anxiety can be facilitating (Frantzen & Magnan, 2005;Gregersen, 2003;Gregersen & Horwitz, 2002;Spielmann & Radnofsky, 2001), findings of most studies have been relatively uniform, indicating a consistently moderate negative relationship between anxiety and SL/FL proficiency/performance (Ewald, 2007;Horwitz, 2001;Liu, 2006b;Liu & Jackson, 2008;Matsuda & Gobel, 2004;Mills, Pajare, & Herron, 2006). For example, Liu and Jackson's (2008) study of 547 Chinese university freshmen revealed that foreign language anxiety was inversely related to the students' self-rated proficiency in and access to English.…”
Section: Foreign Language Anxietymentioning
confidence: 99%
“…Since then, research has been flourishing in this area using the scale as the principal data-collection instrument, agreeing on the existence of anxiety in SL/FL classrooms (Ewald, 2007;Kessler, 2010;Tallon, 2009;Yan & Horwitz, 2008). Though some studies report that anxiety can be facilitating (Frantzen & Magnan, 2005;Gregersen, 2003;Gregersen & Horwitz, 2002;Spielmann & Radnofsky, 2001), findings of most studies have been relatively uniform, indicating a consistently moderate negative relationship between anxiety and SL/FL proficiency/performance (Ewald, 2007;Horwitz, 2001;Liu, 2006b;Liu & Jackson, 2008;Matsuda & Gobel, 2004;Mills, Pajare, & Herron, 2006). For example, Liu and Jackson's (2008) study of 547 Chinese university freshmen revealed that foreign language anxiety was inversely related to the students' self-rated proficiency in and access to English.…”
Section: Foreign Language Anxietymentioning
confidence: 99%
“…However, FLRA does not always affect advanced L2 readers or exert a formative influence on beginning or intermediate L2 readers (Brantmeier, 2005;Frantzen and Magnan, 2005;Sellers, 2000). It was possible that advanced L2 readers were strategic at reading by nature while beginning or intermediate L2 readers invested more effort and time to compensate for their ineffective processing capacity.…”
Section: Test Anxiety and Reading Performancementioning
confidence: 99%
“…Literature in language learning defines "false beginners" (in this article High Beginners, HB) as those language learners who are placed or register themselves in beginner language classes but have already acquired some knowledge-declarative or procedural-of the foreign language in different contexts (Frantzen & Magnan, 2005;Kuriyama, 2014;Nakamura, 1997;Sohn & Shin, 2007). Richards and Schmidt (2010) provide a general definition generally found in most of the literature on HB: "False Beginner: a learner who has had a limited amount of previous instruction in a language but who because of extremely limited language proficiency is classified as at the beginning level of language instruction" (p. 216).…”
Section: High Beginners In the College Spanish Classroommentioning
confidence: 99%
“…Helgesen (1987) describes HB students' can-do abilities considering that "false beginners understand the meaning of a great deal of language and are able to engage in controlled, form-based (accuracy) activities, but their skills are very limited when they get into meaning-focused (fluency) situations" (p. 24). In the particular case of Spanish, this description mostly includes secondlanguage learners (Collentine, 2007;Frantzen & Magnan, 2005;Gascoigne Lally, 2001;Harlow & Muyskens, 1994). These students have taken two or three years of Spanish at high school and are therefore familiar with basic content of the language.…”
Section: High Beginners In the College Spanish Classroommentioning
confidence: 99%
See 1 more Smart Citation